Karakteristik Ibu Yang Mengalami Persalinan Dengan Sectio Caesarea Di Rumah Sakit Umum Daerah Moewardi Surakarta Tahun 2014 - Muhammad, Rasdiana, Dr. Faizah Betty Rahayuningsih, S.Kep., M.Kes, Vinami Yulian, Ns., M.sc (2016)
In Indonesia, sectio caesarea is generally applied when specific medical indications are found, as a measure to resolve a pregnancy with complication. In additio, sectio caesarea is an alternative childbirth for normal pregnancy because it is considered as an easier and compfortable way of giving birth. Sectio caesarea has been administered in 25% of total chidbirths of mothers with no high risk for normal delivery or other complicated deliveries. 2014 in Dr. Moewardi General Hospital, proportion of mothers with sectio caesarea childbirth was 36% or 693 of 1906 childbirths. Purpose of the research was to characteristics of mothers with sectio caesarea childbirth in Dr. Moewardi General Hospital of Surakarta or 2014. The research a descriptive analytical one with sectio caesarea childbirths in Dr. Moewardi General Hospital of Surakarta amounting to 693 individuals. Sample of the research was 87 respondents taken by using systematic random sampling. Checklist was used as an instrument in the research. Data of the research was analyzed by using univariate. Results of the research indicated that the greatest number was found for age group of 20-35 years old, namely 56 respondents (64.4%) Javanese individuals were 80 respondents (92%), respondents with higher education (high school and university) were 63 respondents (72.4%), working mothers were 70 respondents (80.5%), payment system with BPJS were 63 respondents (72.4%), respondents with inter-pregnacy interval of more than 2 years were 46 respondents (52.9%), respondents with good medical history were 56 respondents (64.4%), sectio caesarea with preeclampsia were found in 28 respondents (32.2%), sectio caesarea with indication of fetal distress were found in 25 respondents (28.7%). Results of the research showed that sectio caesarea childbirth has been performed because of not only medical indications, but also sociodemographic faktor and obstetric medico factor should be considered. Keywords : Characteristics of mother, childbirth, Sectio Caesarea